2019
DOI: 10.1111/mmi.14267
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenic actinobacterium Rhodococcus equi: what's in a name?

Abstract: Summary Rhodococcus equi is the only recognized animal pathogenic species within an extended genus of metabolically versatile Actinobacteria of considerable biotechnological interest. Best known as a horse pathogen, R. equi is commonly isolated from other animal species, particularly pigs and ruminants, and causes severe opportunistic infections in people. As typical in the rhodococci, R. equi niche specialization is extrachromosomally determined, via a conjugative virulence plasmid that promotes intramacropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 80 publications
(173 reference statements)
1
65
0
Order By: Relevance
“…The genomic data reveals a typical Rhodococci feature with an approximate size of 8,440,759 bp, a G + C content of 63.28%, 8462 protein-coding sequences (CDs), 6 rRNA and 82 tRNAs genes. The large size and high CDs of the draft genome are believed to be associated with the extensive actinobacterial chromosome linearisation and dependent to the host itself, which are isolated from an extreme niche (Antarctic soil) [ 46 ]. The annotated data also shows a high similarity with two other known genomes of R. erythropolis (PR4 and CCM2925) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The genomic data reveals a typical Rhodococci feature with an approximate size of 8,440,759 bp, a G + C content of 63.28%, 8462 protein-coding sequences (CDs), 6 rRNA and 82 tRNAs genes. The large size and high CDs of the draft genome are believed to be associated with the extensive actinobacterial chromosome linearisation and dependent to the host itself, which are isolated from an extreme niche (Antarctic soil) [ 46 ]. The annotated data also shows a high similarity with two other known genomes of R. erythropolis (PR4 and CCM2925) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…nov. by Kämpfer et al [12], which involved polyphasic taxonomic analyses that included the type strains C. hoagii DSM 20295 T (=ATCC 7005 T ) and R. equi DSM 20307 T (=ATCC 6939 T ). These studies (i) confirmed the identity of R. equi DSM 20307 T and C. hoagii DSM 20295 T as the same species while (ii) they did not find distinct chemotaxonomic differences or 16S rDNA-based phylogenetic separation from other rhodococci to justify the reclassification of R. equi into a new genus 'Prescotella' [12] (consistent with compelling phylogenomic evidence [13,14]). In application of the principle of priority of the International Code of Nomenclature of Prokaryotes, aka the 'Prokaryotic code' [15], Kämpfer et al proposed to reclassify Corynebacterium hoagii and Rhodococcus equi as Rhodococcus hoagii comb.…”
Section: Conservation Of Rhodococcus Equimentioning
confidence: 55%
“…In contrast, the equi epithet has been in widespread use and constantly associated with its cognate bacterial species since its discovery in 1923 by H. Magnusson as the causative agent of a severe infectious disease of foals [26,27]. While R. equi can also cause opportunistic human infections and colonize other animal species [14,17,18,[28][29][30], it remains best known as a major horse pathogen and thus the epithet is aptly descriptive of the species [31,32]. Indeed, the name R. equi has a solid standing in veterinary and human medicine, animal science and the equine industry, and the change to R. hoagii is disconcerting and likely to hamper the traceability and interpretation of the medical, scientific and technical literature regarding this pathogen.…”
Section: Conservation Of Rhodococcus Equimentioning
confidence: 99%
See 2 more Smart Citations